2015
DOI: 10.16970/ted.34407
|View full text |Cite
|
Sign up to set email alerts
|

Determination of insecticide resistance of European grapevine moth [Lobesia botrana (Denis & Schiffermüller) (Lepidoptera: Tortricidae)] populations in vineyards of Manisa province

Abstract: SummaryThis study was carried out to determine the resistance to insecticides of European Grapevine Moth, the main pest of vineyards between 2011-2014. Using the diet method, Lethal Concentration (LC) values of four different insecticides were determined in 10 different European Grapevine Moth populations and then the resistance coefficients were calculated comparing these values with susceptible population. LC50 values were about 6 fold for chlorpyrifos-ethyl in Sarıgöl-2 population, about 5 fold for deltamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 13 publications
2
6
2
Order By: Relevance
“…The difference in LC50 values suggests that AL has more susceptibility to chlorpyrifos-ethyl than SAR population. Previously, a similar trend was observed among the field populations, which suggests that L. botrana susceptibility varies in different grapevine production regions (Hatipoglu et al 2015). This might indicate that production areas in SAR or surrounding areas could potentially face a resistant population against chlorpyrifos-ethyl in the near future.…”
Section: Insecticide Efficacysupporting
confidence: 78%
See 3 more Smart Citations
“…The difference in LC50 values suggests that AL has more susceptibility to chlorpyrifos-ethyl than SAR population. Previously, a similar trend was observed among the field populations, which suggests that L. botrana susceptibility varies in different grapevine production regions (Hatipoglu et al 2015). This might indicate that production areas in SAR or surrounding areas could potentially face a resistant population against chlorpyrifos-ethyl in the near future.…”
Section: Insecticide Efficacysupporting
confidence: 78%
“…Several reports are available on insecticide efficacy of L. botrana developmental stages and detoxification enzymatic levels (Irigaray et al 2005;Vassiliou 2011;Civolani et al 2014;Pavan et al 2014;Hatipoglu et al 2015;Navarro-Roldan et al 2017;Pasquini et al 2018;Navarro-Roldan et al 2020). Several reports are available regarding insecticide toxicity on L. botrana (Irigaray et al 2005;Vassiliou 2011;Pavan et al 2014;Hatipoglu et al 2015;Pasquini et al 2018) however, up until now, there is only one insecticide resistance report available for L. botrana (Civolani et al 2014). For that reason, it is important to monitor the insecticide efficacy to provide optimal L. botrana control and mitigate the potential resistance development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, testing four different insecticides against ten EGM populations from Manisa vineyards using diet incorporation showed that Ahmetli and Alasehir populations were potentially resistant to indoxacarb (Hatipoglu et al, 2015). A high resistance was also detected in Italy using the same bioassay method (Civolani et al, 2014).…”
Section: Merkez 1 540mentioning
confidence: 56%